2012
DOI: 10.1371/journal.pone.0044232
|View full text |Cite
|
Sign up to set email alerts
|

Increased Responsiveness of Peripheral Blood Mononuclear Cells to In Vitro TLR 2, 4 and 7 Ligand Stimulation in Chronic Pain Patients

Abstract: Glial activation via Toll-like receptor (TLR) signaling has been shown in animals to play an important role in the initiation and establishment of chronic pain. However, our ability to assess this central immune reactivity in clinical pain populations is currently lacking. Peripheral blood mononuclear cells (PBMCs) are an accessible source of TLR expressing cells that may mirror similarities in TLR responsiveness of the central nervous system. The aim of this study was to characterize the IL-1β response to var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 48 publications
2
72
1
Order By: Relevance
“…Further, IC/BPS is marked by inflammatory dysregulation, indicated by flattened diurnal cortisol rhythmicity, elevated plasma IL-6 and an exaggerated IL-1β response to TLR-2 stimulation in PBMCs. TLR-2 stimulated IL1-β responses in PBMCs were recently shown to be capable of differentiating a population of chronic pain patients from HCs [19]. This study extends that finding to a chronic pelvic pain population.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Further, IC/BPS is marked by inflammatory dysregulation, indicated by flattened diurnal cortisol rhythmicity, elevated plasma IL-6 and an exaggerated IL-1β response to TLR-2 stimulation in PBMCs. TLR-2 stimulated IL1-β responses in PBMCs were recently shown to be capable of differentiating a population of chronic pain patients from HCs [19]. This study extends that finding to a chronic pelvic pain population.…”
Section: Discussionsupporting
confidence: 75%
“…Plasma cytokines were assayed with high sensitivity Quantikine ELISAs. Similar approaches in populations with complex presentations of pain have been reported and are able to distinguish patients from healthy controls [5,16,17,19]. …”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…One prospective study found that a blunted diurnal cortisol rhythm and non-suppression of the HPA axis were associated with new-onset chronic widespread pain among psychologically at-risk subjects 5. Also, IMS dysfunction has been demonstrated in chronic pain 11. We recently found unaltered levels of basal inflammatory markers but elevated levels of lipopolysaccharide (LPS)-stimulated inflammatory markers in chronic multisite musculoskeletal pain, possibly indicative of an enhanced innate immune response 12.…”
Section: Introductionmentioning
confidence: 95%
“…These findings are, suggestive of immune alterations in human pain states and enhancement by opioids. 114 …”
Section: Neuroimmune Interactions In Painmentioning
confidence: 99%